Implementasi pemasaran digital berbasis website sebagai strategi kenormalan baru Dusun Srumbung Gunung pasca Covid-19 - Evi Maria; Suharyadi Suharyadi; Rini Kartika Hudiono (Riau Journal of Empowerment, 2021)
Covid-19 has an impact on the decrease in trading activity in Dusun.Srumbung Gunung, because marketing activities still rely on physical stores. The purpose of community service activities is to develop a Pasar Dusun website and train website administrators welcoming the new normality. This activity was carried out with a descriptive approach using two methods. First, mentoring was done to start the Website of Pasar Dusun. Second, the training of administrators who are in charge and responsible for managing trade transactions that occur on the website of Pasar Dusun was carried on. The result of this activity is the availability of a Dusun Market website that can be accessed on https://pasardusun.sakoo.id/. Since, August 13, 2020 to September 19, there have been 9 successful trade transactions on the website of Pasar Dusun with a total of 165 products sold. This shows the contribution of digital marketing to increase the income of villagers after Covid-19. The results of the training of administrators, website managers have been able to maintain and update information related to buying and selling activities on the website of Pasar Dusun.